2022
DOI: 10.31146/1682-8658-ecg-196-12-35-43
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome therapy in Vietnam with probiotic enterococci

Abstract: In this work, we compared composition of the intestinal microbiota of healthy volunteers and patients with irritable bowel syndrome (IBS) in Hanoi residents before and after therapy with a probiotic starter culture based on the bacteriocinogenic strain Enterococcus faecium L3 (L3), which is successfully used to correct dysbiosis and treat IBS in Russia.In IBS patients (IBS group) α-diversity was higher than in the control group (Healthy) and in IBS patients after probiotic therapy (IBS + L3 group). Phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The correction of dysbiosis was accompanied by a stimulation of anti-inflammatory cytokines IL-10, TGF-β, and a reduction in proinflammatory cytokines MCP1 and IL-8 [35]. The same model shows a beneficial effect of autoprobiotics on intestinal motility [70]. Also, we demonstrated that autoprobiotic intake contributes to a decrease in dyspeptic symptoms and is associated with positive changes in the gut microbiota content [71,72], as well as the vaginal microbiota content [73].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The correction of dysbiosis was accompanied by a stimulation of anti-inflammatory cytokines IL-10, TGF-β, and a reduction in proinflammatory cytokines MCP1 and IL-8 [35]. The same model shows a beneficial effect of autoprobiotics on intestinal motility [70]. Also, we demonstrated that autoprobiotic intake contributes to a decrease in dyspeptic symptoms and is associated with positive changes in the gut microbiota content [71,72], as well as the vaginal microbiota content [73].…”
Section: Discussionsupporting
confidence: 67%
“…A special feature of this study was the additional use of E. hirae, which we first discovered as candidates for autoprobiotic agents in Vietnam [80,81], and after that, in Russia for patients with CRC.…”
Section: Discussionmentioning
confidence: 99%